Alpha Phi Alpha : a legacy of greatness, the demands of transcendence - Parks, Gregory, 1974-; Bradley, Stefan M. (University Press of Kentucky, 2012)
"On December 4, 1906, seven black men ... founded one of the greatest and most enduring organizations in American history on the campus of Cornell University. ... Alpha Phi Alpha was founded to instill a spirit of high academic achievement and intellectualism, foster meaningful and lifelong ties, and invoke the desire for racial uplift in those brothers who would join its ranks. ... [The] editors have assembled a team of scholars to analyze the fraternity and its fidelity to the founding precepts set forth in 1906"--Publisher's description